A Probabilistic Model of User Navigation in a Digital Interactive Publication - Darbinyan, Vahram H. (Mathematical Problems of Computer Science, 2021)
A probabilistic model of user navigation in a digital interactive publication is considered. Digital interactive publication is a paged media where user can navigate either by flipping pages back and forth or using a link for navigation to another page. User’s navigation by links is analyzed in detail. For that case a special weight is assigned to any navigation from the current page to another page. A method of calculating these weights is proposed basing on a publication type and structure. Considerations include both server-side and client-side analysis. A mapping of the introduced weights to probabilities of navigation to each page is proposed also. These probabilities allow predicting user behavior during the paged media navigation. Experiments with a representative sample set of digital publications have been performed to illustrate the validity of the suggested model.